Developing an Automatic Ontology Constructor for Bahasa Indonesia Using Cognitive Approach: A Proposal - Virginia, Gloria; Nguyen, Hung Son (Proceedings of KNASTIK, 2010)
There are great challenges in computer linguistic and information retrieval fields which process Bahasa Indonesia.  Taking advantage from implementation of Linear Model life cycle, an automatic ontology constructor (OC) is going to be generated.  The natural language in emails together with the exhaustive cognitive approach argues to be essential in the process of OC generation that one may achieve deep linguistic analysis.  An ontology-based information retrieval system for Indonesian choral community is going to be developed using 3,000 emails of Indonesian Choral Lovers (ICL) mailing list as a tool of evaluation.  Performance measure of information retrieval (recall and precision) and qualitative measure of ontology (consistency, completeness, and conciseness) are going to be used to find out the OC effectiveness through examining the automatic-thesaurus effectiveness. The associative thesaurus generated manually and automatically will also enrich the IndonesianWordNet being struggled.